(untitled) (Bangladesh Journal of Medical Science, 2014)
With decreasing incidence of cervical pathology in western world due to increasing awareness and screening programme. Contrary to it in India and developing countries cervical lesion, particularly cervical carcinoma is the leading cause of increasing morbidity, mortality and financial burden on society. The present study is an insight into the epidemiological profile of cervical lesion on Pap smear and histopathology finding in Kosi region of Bihar. The study was carried over the period of 2 years 8 months. Total 154 patients were enrolled in this study and were analysed for age, socio-economic status, parity, age at first pregnancy and symptoms using Pap smear with histopathological finding of cervical lesions. Data were analysed of which 79.23% (122) patients were in age groups 21-40 years, 72.08% (111) were from low socio-economic status, and 70.78% (109) were with parity 4 and more. 66.88% (103) patients delivered their first child below 20 years of age. 69.49% (107) patients presented with foul smelling vaginal discharge and pelvic pain. On pap smear and histopathological findings preinvasive (dysplasia, LGSIL, HGSIL) and invasive stage (carcinoma) constituted 26.61% (41) cases. The epidemiological pattern of cervical lesion in kosi region of Bihar is different from other study with presentation in younger age groups, high parity and markedly increased incidence of premalignant and malignant lesion on pap smear and histopathology findings. DOI: http://dx.doi.org/10.3329/bjms.v13i4.16641 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.427-430